Occupational Exposures in the Homecare Environment: Piloting an Observation Tool. Issue 3 (August 2021) - Bien, Elizabeth; Davis, Kermit; Reutman, Susan; Gillespie, Gordon
The population of home healthcare workers (HHCWs) is rapidly expanding. Worker tasks and the unique home care environments place the worker at increased risks of occupational exposures, injury, and illness. Previous studies focusing on occupational exposures of HHCWs are limited to self-reports and would benefit from direct observations. The purpose of this study is to describe the occupational hazards observed in the unique work environment of home healthcare. HHCWs and home care patient participants were recruited from one home care agency in the Midwest to be observed during a routine home visit. This cross-sectional study used a trained occupational health nurse for direct observation of the occupational setting. Standardized observations and data collection were completed using the Home Healthcare Worker Observation Tool. The observer followed a registered nurse and occupational therapist into 9 patient homes observing visits ranging from 22 to 58 minutes. Hazards observed outside of and within the home include uneven pavements (n = 6, 67%), stairs without railings (n = 2, 22%), throw rugs (n = 7, 78%), unrestrained animals (n = 2, 22%), dust (n = 5, 56%), and mold (n = 2, 22%). Hand hygiene was observed prior to patient care 2 times (22%) and after patient care during 5 visits (56%). Observations have identified hazards that have the potential to impact workers' and patients' health. The direct observations of HHCWs provided opportunities for occupational safety professionals to understand the occupational exposures and challenges HHCWs encounter in the home care environment and begin to identify ways to mitigate occupational hazards.